Opportunities for Drug Repurposing of Serotonin Reuptake Inhibitors: Potential Uses in Inflammation, Infection, Cancer, Neuroprotection, and Alzheimer’s Disease Prevention - Nykamp, Madeline J.; Zorumski, Charles F.; Reiersen, Angela M.; Nicol, Ginger E.; Cirrito, John; Lenze, Eric J. (Pharmacopsychiatry, 2021)
Serotonin reuptake inhibitors (SRIs) are safe and widely used for a variety of indications including depressive disorders, anxiety, and chronic pain. Besides inhibiting the serotonin transporter, these medications have broad-spectrum properties in many systems. Their roles have been studied in cancer, Alzheimer’s disease, and infectious processes. The COVID-19 pandemic highlighted the importance of drug repurposing of medications already in use. We conducted a narrative review of current evidence and ongoing research on drug repurposing of SRIs, with a focus on immunomodulatory, antiproliferative, and neuroprotective activity. SRIs may have clinical use as repurposed agents for a wide variety of conditions including but not limited to COVID-19, Alzheimer’s disease, and neoplastic processes. Further research, particularly randomized controlled trials, will be necessary to confirm the utility of SRIs for new indications.
Keywords: Selective serotonin reuptake inhibitors (SSRIs); Drug Repurposing; Alzheimer-s disease (AD); COVID 19; Antiinflammatory agents